Role of technology in athlete assessment - De Groot, S.; Mason, B.; Vegter, R.; Haydon, D. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
Many factors play a role in talent development such as task characteristics, environment and performance characteristics. Chapter 11 focusses on the role of technology in athlete assessment. As described in this chapter, technology can be used for testing and monitoring performance characteristics such as anthropometric, physiological, technical, and tactical skills applicable to Para sports. When monitoring these aspects over time, individual performance curves on each characteristic can be made. Furthermore, these scores of an athlete can be compared to earlier scores as well to reference data of a similar group. Combining data of several performance characteristics over time can give valuable practical information concerning talent development.